A defect in COPI-mediated transport of STING causes immune dysregulation in COPA syndrome - Deng, Zimu; Chong, Zhenlu; Law, Christopher S.; Mukai, Kojiro; Ho, Frances O.; Martinu, Tereza; Backes, Bradley J.; Eckalbar, Walter L.; Taguchi, Tomohiko; Shum, Anthony K. (The Journal of experimental medicine, 2020)
Pathogenic COPA variants cause a Mendelian syndrome of immune dysregulation with elevated type I interferon signaling. COPA is a subunit of coat protein complex I (COPI) that mediates Golgi to ER transport. Missense mutations of the COPA WD40 domain impair binding and sorting of proteins targeted for ER retrieval, but how this causes disease remains unknown. Given the importance of COPA in Golgi–ER transport, we speculated that type I interferon signaling in COPA syndrome involves missorting of STING. We show that a defect in COPI transport causes ligand-independent activation of STING. Furthermore, SURF4 is an adapter molecule that facilitates COPA-mediated retrieval of STING at the Golgi. Activated STING stimulates type I interferon–driven inflammation in CopaE241K/+ mice that is rescued in STING-deficient animals. Our results demonstrate that COPA maintains immune homeostasis by regulating STING transport at the Golgi. In addition, activated STING contributes to immune dysregulation in COPA syndrome and may be a new molecular target in treating the disease.